1983
DOI: 10.2337/diab.32.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Insulin by Monkey and Pig Hypothalamus

Abstract: Membrane preparations from monkey and pig hypothalami bound [125I]insulin specifically. The binding appeared to be greater by preparations from anterior than posterior portions of the pig hypothalamus. Binding was time dependent, and its dissociation was first order with a half-time at 22 degrees C of 14 min. Desalanine insulin was as effective as native insulin in inhibiting the binding of [125I]insulin, while proinsulin was less effective and desoctapeptide insulin still less effective in accord with their b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Since then, a wide but uneven distribution of IR in the CNS has been reported. Accordingly, it was shown that membrane preparations from the hypothalami specifically bound greater [ 125 I]insulin than membranes from the cortex and thalamus, and that this binding was higher for preparations from the anterior rather than the posterior portions of the hypothalamus ( 54 ). Likewise, the binding of [ 125 I]insulin was high not only in all olfactory areas and in closely related limbic regions, but also in the neocortex and accessory motor areas of the basal ganglia, hippocampus, cerebellum, and choroid plexus, which suggested a neuromodulatory function for insulin in the brain ( 55 ).…”
Section: Mechanisms Of Insulin Signal Transduction In the Brainmentioning
confidence: 99%
“…Since then, a wide but uneven distribution of IR in the CNS has been reported. Accordingly, it was shown that membrane preparations from the hypothalami specifically bound greater [ 125 I]insulin than membranes from the cortex and thalamus, and that this binding was higher for preparations from the anterior rather than the posterior portions of the hypothalamus ( 54 ). Likewise, the binding of [ 125 I]insulin was high not only in all olfactory areas and in closely related limbic regions, but also in the neocortex and accessory motor areas of the basal ganglia, hippocampus, cerebellum, and choroid plexus, which suggested a neuromodulatory function for insulin in the brain ( 55 ).…”
Section: Mechanisms Of Insulin Signal Transduction In the Brainmentioning
confidence: 99%
“…Intranasal delivery (IND) of insulin provides a safe, feasible, and effective route of administration, largely bypassing the blood-brain barrier (BBB) and maximizing distribution to the CNS [5]. Insulin receptor (IR) kinase is located throughout the brain and with high density in the olfactory bulb (OB), piriform cortex, hypothalamus, and hippocampus [6]; brain areas that also happen to have a high binding affinity for insulin [7,8,9]. Peripheral insulin is thought to bypass the BBB, via a saturable, active transport system [10, 11] allowing binding of insulin to IR kinase to elicit dimerization of the receptor followed by autophosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, membrane preparations from the monkey and pig hypothalami showed higher 125 I-insulin-binding activity in the anterior rather than the posterior parts of the hypothalamus [59]. High 125 I-insulin-binding activity was also detected all olfactory areas, limbic regions, neocortex and accessory motor areas of the basal ganglia, hippocampus, cerebellum, and choroid plexus, which suggested a regulatory role of insulin in the brain [60].…”
Section: Ir Expression In the Cns And Its Signaling Pathwaysmentioning
confidence: 99%